Pemberdayaan Masyarakat dalam Meningkatkan Kesadaran Bela Negara melalui Edukasi Pertahanan di Lingkungan Kampus dan Komunitas Lokal - Franceline Adella; Aris Sarjito; Agus Sudarya (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
Amidst contemporary challenges such as radicalism and disinformation, the awareness of defending the nation (Bela Negara) remains a critical yet underdeveloped foundation for Indonesia’s national resilience, particularly among the youth. Existing educational approaches are often perceived as merely ceremonial, failing to instill a deep sense of practical national values. This study aims to analyze the role of community empowerment through defense education in enhancing the awareness of defending the nation within university campuses and local communities. Employing a qualitative approach with a literature review design, this research systematically analyzes data from various academic sources. The findings reveal that a synergistic collaboration between universities, as centers for human resource and technology development, and local communities, as the bedrock of non-military defense, strengthened by local wisdom, is a highly effective strategy. This approach transforms the concept of defending the nation from a formal obligation into active, practical engagement, empowering citizens with the necessary skills to counter modern non-military threats. The strategic implication of this empowerment model is the reinforcement of a comprehensive total people’s defense system (Sishankamrata), thereby strengthening national resilience against a broad spectrum of contemporary threats and fostering a more participatory defense ecosystem.